Assessing the Gender Impacts and Contributions of CCAFS Climate-Smart Villages in Lao PDR - Vivona, Dina; Thipphawong, Elizabeth (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
From July – September 2021, a Gender Impact Assessment (GIA) was conducted to measure the impacts of the CSV gender strategy in regards to project participation, agricultural productivity, and overall socio-economic impacts at the village-cluster level. The GIA also aimed to provide insight on the impacts of the global COVID-19 pandemic on project objectives, and more specifically, women’s coping strategies as they relate to Climate-Smart Villages. Primary data was collected from two villages in Savannakhet Province, Lao PDR, and included a total of 28 respondents (9 female, 19 male). Although all respondents reported positive impacts to their livelihoods and improved resilience to climate change-related challenges, the CSV did not achieve gender-transformative outcomes. This is likely the result of a gender strategy which emphasized equal participation without improving knowledge on gender equality principles or fostering an enabling environment for social behaviour change. Also, since the CSV gender strategy did not include specific gender development targets, it could not be determined whether gender-specific outcomes were reached. This highlights the need for long-term systemic gender strategizing across sectors, programmes, and partnerships.